2020
DOI: 10.4028/www.scientific.net/jbbbe.47.1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicon- and Carbonate-doped Biomimetic Hydroxyapatite in the Presence of Citrate Ions and its Physicochemical, Bioactivity Properties

Abstract: The present study investigated the phase composition, the structural, morphological, and bioactivity properties of silicon- and carbonate-doped biomimetic hydroxyapatite synthesized by precipitation from aqueous solutions in the presence of different amounts of citrate ions. The X-ray diffraction and Fourier transform infrared spectroscopy analyses confirmed that all the samples exhibited single-phase. Base on the results of the morphological study, all the obtained samples consisted of porous agglomerated par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The weak bands of BpNcCaPs at 1,415-1,419 cm −1 and 866-872 cm −1 might be assigned to carbonate. Carbonates are constituents of bone structures, whose presence may improve the bioactivity of HA (Vallet-Regi and González-Calbet, 2004;Hoang et al, 2020). According to the literature (Fahami et al, 2012;Ignjatović et al, 2019;Edén, 2021), the functional groups generally observed in the FTIR spectra of CaP-based materials are PO 4 3-, OH − and CO 3 2groups in the range 4000-300 cm −1 .…”
Section: Surface Spectra Of Bpnccapsmentioning
confidence: 99%
“…The weak bands of BpNcCaPs at 1,415-1,419 cm −1 and 866-872 cm −1 might be assigned to carbonate. Carbonates are constituents of bone structures, whose presence may improve the bioactivity of HA (Vallet-Regi and González-Calbet, 2004;Hoang et al, 2020). According to the literature (Fahami et al, 2012;Ignjatović et al, 2019;Edén, 2021), the functional groups generally observed in the FTIR spectra of CaP-based materials are PO 4 3-, OH − and CO 3 2groups in the range 4000-300 cm −1 .…”
Section: Surface Spectra Of Bpnccapsmentioning
confidence: 99%
“…It was also reported [21,22] that the addition of citrate ions (Cit 3-) into the reaction medium during HAP synthesis changes the structural and morphological characteristics of the product materials. Citrate ions participating in biological cycles play an important role in bone tissue resorption and bioapatite formation, for example, during the nanoscale stabilization of HAP crystallites in bone [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%